Measures of Technology and the Business Cycle - Annika Alexius; Mikael Carlsson (Uppsala University, Department of Economics, 2002)
Empirical evidence on the relationship between technology shocks and e.g. hours worked hinges crucially on the identification of the unobservable technological progress. In this paper, we study different measures of technology in order to find out (i) to what extent they capture the same underlying phenomenon and (ii) whether the implications for macroeconomic theory are robust across the approaches. Several versions of the productions function approach and structural VAR models are investigated. Our main finding is that the different technology measures are highly correlated. However, the exact formulation of the identifying restrictions seems to matter for the results. While we replicate the standard finding of a strongly procyclical Solow residual, all other measures of technology are either acyclical or countercyclical.
urn:nbn:se:uu:diva-2230
Keywords: C32; E32; 330; Technology shocks; productions function approach; strcture VAR models; Technischer Fortschritt; Schock; Produktionsfunktion; VAR-Modell; Theorie